2006
DOI: 10.1093/europace/eul049
|View full text |Cite
|
Sign up to set email alerts
|

Electrical storm of monomorphic ventricular tachycardia after a cardiac-resynchronization-therapy-defibrillator upgrade

Abstract: In patients with significant left ventricular dysfunction and congestive heart failure despite optimal medical therapy, implantation of cardiac resynchronization therapy-defibrillation (CRT-D) devices has been shown to improve symptoms and mortality. In this report, we describe a case of a patient with ischaemic cardiomyopathy who developed incessant ventricular tachycardia (VT) after undergoing an upgrade from an implantable cardioverter defibrillator to a CRT-D device. The patient required multiple anti-arrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Some authors have suggested that prolongation of the transmural dispersion of repolarization, by reversal of the activation sequence caused by LV epicardial pacing, can promote polymorphic VT 9,10 while others have indicated re-entry as the likely mechanism. 4,8 We report our experience in managing CRT-induced proarrhythmia with catheter ablation and postulate that pacing from the epicardium using an LV lead positioned on scar could influence critical components of a re-entrant circuit and induce re-entrant VT. For that purpose, the relationship between CRT-induced proarrhythmia and LV lead tip location within scar was investigated.…”
Section: Editorial See P 1000 Clinical Perspective On P 1069mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested that prolongation of the transmural dispersion of repolarization, by reversal of the activation sequence caused by LV epicardial pacing, can promote polymorphic VT 9,10 while others have indicated re-entry as the likely mechanism. 4,8 We report our experience in managing CRT-induced proarrhythmia with catheter ablation and postulate that pacing from the epicardium using an LV lead positioned on scar could influence critical components of a re-entrant circuit and induce re-entrant VT. For that purpose, the relationship between CRT-induced proarrhythmia and LV lead tip location within scar was investigated.…”
Section: Editorial See P 1000 Clinical Perspective On P 1069mentioning
confidence: 99%
“…3 Despite this, CRT-induced proarrhythmia has been reported as a clinically serious, rare, and unpredictable phenomenon. [4][5][6][7] Patients usually present with recurrent sustained ventricular tachycardia (VT)/electrical storm (ES), refractory to antiarrhythmic drugs, often accompanied with HF deterioration and cardiogenic shock. 7 Although suppression of recurrent VT with catheter ablation has been reported, 7,8 treatment most often required inactivation of LV pacing, depriving these patients of the beneficial effects of resynchronization.…”
mentioning
confidence: 99%
“…31 Cases have been reported of CRT inducing ventricular arrhythmias, but several trials report a reduction in these events. [32][33][34][35][36] A review of the 2 largest CRT trials did not show significant increases or decreases in ventricular arrhythmia. 37 …”
Section: Patient Selection and Therapeutic Resultsmentioning
confidence: 99%
“…The aetiology of electric storm is not clearly understood. The factors contributing to storm onset are: worsening of cardiac function, electrolyte disturbance, autonomic imbalance, drug proarrhythmia, a context with other illness, psychological stress, excess ethanol consumption and cardiac resynchronization therapy (Kantharia et al, 2006). In 35% of the patients storms represent their first event.…”
Section: Icd-specific Complicationsmentioning
confidence: 99%